Vozes dos professores do primeiro ciclo sobre o ensino de ciências em uma escola municipal de Cuiabá-MT - Santos, Alvarina de Fátima dos (2019)
In a social context distinguished by the scientific and technological advances, it is crucial to understand science as a human production, and, in this perspective, to teach and to learn Natural Sciences in all grades of Elementary Education. In this work, we aim to analyze what elementary education teacher tell about what and how they teach natural sciences? The investigation took place at a public school in the city of Cuiabá-MT, which we call Escola Rio Coxipó, with the participation of three teachers who give lessons for the 1st, 2nd and 3rd years of Elementary Education. We followed a qualitative research method, with an exploratory study and, to produce study data, we used as research instruments and procedures: school documents analysis, questionnaire, interview, classroom observation and the field notebook. The research was carried out during one semester and during this period we watched 20 days of proposed classes, of which half were taught. The theoretical assumptions for the foundation of the research are based on the scientific understanding that the human being is a producer of knowledge and actions in its relationship with the natural, social, historical and cultural environment where he lives. Thus, we dialogue with Chalmers (1993), who discusses science; Krasilchik (1987), Bizzo (2009, 2012) addresses the historicity of science teaching and its curricular relation of pedagogical formation; Angotti (1990), who express their ideas about methodology of science teaching; Trivelato, Silva e Carvalho (2011), Fracalanza, Amaral and Gouveia (1986), who reference approaches on natural sciences teaching on elementary schools; Lorenzetti (2001), Sasseron; Carvalho (2011), Chassot (2014), who conceptualize Scientific Literacy as opportunity to acknowledge and transform the world, from the reality experienced; The results show that teachers teach contents related to biological knowledge - plants, animals, human body; about the natural aspects – environment, soil, water, energy; social aspects: food culture, health, disease prevention, environmental conservation involving the fauna, the flora, water sources, soil. The education is mediated by the exposition of ideas, dialog with the students and field observation. The systematization of knowledge is done in drawings, cut and paste, objective exercises that students complete, with or without teaching aid. We comprehend about what and how they teach are scientific concepts with procedures that allow the appropriation and not the knowledge production by the children, considering the historical and cultural context. We believe that the result of this research will contribute to the didactic, pedagogical and formative discussions at scholar, institutional and academical levels, on the importance of science teaching in the initial years of elementary education.